1991
DOI: 10.1111/j.1439-0329.1991.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

New type forest damage to mediterranean vegetation in Southern Sardinian forests (Italy)

Abstract: This paper investigates some biological aspeets of the decline of the Forest of Pilcinamanna in Southern Sardinia: the evolution of forest deterioration, leaf diagnosis, analysis and observation with SEM. We present the hypothesis of a relationship between this decline and some adverse environmental faetors, particularly atmospheric pollution and drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The pathogenicity of P. cinnamomi to the various Mediterranean oak species, and to some Mediterranean maquis trees and shrubs also exhibiting symptoms of decline (c.f. Bussotti et al, 1991) now needs to be tested or confirmed, and its degree of association with decline and interaction with other site factors subject to detailed study. By analogy, P. cinnamomi may also be associated with the current rapid mortality of Q. suber, Q. cerris and other Quercus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of P. cinnamomi to the various Mediterranean oak species, and to some Mediterranean maquis trees and shrubs also exhibiting symptoms of decline (c.f. Bussotti et al, 1991) now needs to be tested or confirmed, and its degree of association with decline and interaction with other site factors subject to detailed study. By analogy, P. cinnamomi may also be associated with the current rapid mortality of Q. suber, Q. cerris and other Quercus spp.…”
Section: Discussionmentioning
confidence: 99%
“…On both older plants and damaged plants, weathering caused the coalescence of the waxy fibrils above the stomata, and ultimately the stomatal plug was lost (Grieve and Pitman 1978). Degraded waxes and stomata ''filled up with melted wax'' of Quercus ilex were also reported (Bussotti et al 1991). In Pinus needles, sea salt and surfactant deposition led to changes in water content and midday water potential, indicating interference in water relations (Nicolotti et al 2005).…”
Section: Particles As Desiccantsmentioning
confidence: 99%
“…Wax structure has been used as a phytopathological bioindication. The effect of rain and wind on structural wax degradation appears to be enhanced at polluted sites where dust, soot and/or salts are present (BUSSOTTI et al 1991). The correlation between structural wax degradation and the amount of needles on the trees (GRILL et al 1987), or with needle discolouration (HASEMANN et al 1990) may either parallel needle water-content (BADOT and GARREG 1990) or may refiect environmental exposure (GAPE et al 1989).…”
Section: Introductionmentioning
confidence: 99%